PENGARUH PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR PENGHASIL BAHAN BAKU SUB-SEKTOR LOGAM DAN MINERAL DI BURSA EFEK INDONESIA TAHUN 2019-2020 - Irma Suryani; Lorina Siregar Sudjiman (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
This study aims to analyze and see how the effect of tax planning on earnings management in raw materials and minerals sub-sector companies listed on the IDX for the 2019-2020 period. The sampling thecnique was carried out by selected purposive sampling 15 companies for 2 years and the namber of samples is 23 companies. The source of data in study is secondary data downloaded throught the official website of the IDX. This type of research is descriptive analysis method and the type of research is quantitative research. The data analysis technique in this study used multiple linear regression analysis. Processing data using SPSS and performing several stages of analysis, namely descriptive statiscal test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, determination test. T test and F test. The result of this study indicate that simultaneously tax planning has no significant effect on earnings management in metal and mineral sub-sector manufacturing companies that produce raw material listed on the Indonesia Stock Exchange for the 2019-2020 period.